Anxiety Levels of Preschool Children on the Effect of Play Therapy Due to Hospitalization at Makassar City Hospital - Mesa, Novita Dewi Kok; Mutiah, Cut; Aripa, Lusyana; Muchsin, Wachyudi; Kurniawati, Kurniawati; Megasari, Anis Laela (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hospitalization is often the first thing children have to face, especially during the early years, especially vulnerable to illness and hospitalization crises due to stress due to changes in health conditions, as well as children have a limited number of coping mechanisms to resolve stressors. The intervention This can be done, one way is by playing activities or play therapy. In sick condition or the child is hospitalized, this play activity is still carried out but must be appropriate with the child's condition. With games, children will be released from tension and stress experienced, because by playing children will be able to divert the pain on the game and relaxation through the pleasure of playing the game. The aim of this research is to determine the effect of play therapy on levels worry child on age preschool consequence hospitalization in Makassar Hospital. This research uses quantitative research methods with design study quasy experiment. Population in study This is all over child preschool in the Makassar Hospital Treatment Room with a sample of 20 pre-school children. From the results of the Wilcoxon test which was carried out with a value of p = 0.008, means mark p more small from α (0.05) Which show There is change response worry child before given therapy play And after given play therapy. Researchers hope for hospitals to implement play therapy to reduce anxiety levels in children and this research can be useful for respondents, especially parents, that play therapy very helpful for child in reduce level worry.